Analisis Pengaruh Konsentrasi Larutan Alkali Terhadap Perubahan Diameter Serat Sabut Kelapa - Arsyad, Muhammad; Salam, Abdul (Politeknik Negeri Ujung Pandang, 2017)
Abstract—The goals of this study was to determine the effect of alkali concentration in the soaking coconut coir fiber (S2K) to changes in coconut fiber diameter. Stages of implementation of the study are (1) the measurement of the diameter of S2K before soaking, (2) immersion S2K in an alkali solution (NaOH) at a concentration of 5%, 10%, 15%, 20%, and 25% for 3 and 5 hours, ( 3) after being soaked, S2K removed and rinsed with distilled water, (4) was dried in a room temperature of 30±2°C for 5 days, (5) the measurement of the diameter of S2K after soaking with digital microscope. Based on the results of tests performed concluded that (1) immersion in an alkali solution resulted in a reduction of the diameter of S2K, (2) on soaking 5 hours at a concentration of 15% NaOH solution obtained reduction diameter S2K largest percentage of 56.08%. Keywords: natural fibers, the concentration of alkali, wettability.